2021
DOI: 10.3389/fevo.2021.634754
|View full text |Cite
|
Sign up to set email alerts
|

Parasite-Modified Chemical Communication: Implications for Aquatic Community Dynamics

Abstract: Chemical communication within an aquatic environment creates an intricate signaling web that provides species with information about their surroundings. Signaling molecules, like oxylipins, mediate a multitude of interactions between free-living members of a community including non-consumptive effects by predators. Parasites are another source of signaling molecules in aquatic communities and contribute directly by synthesizing them or indirectly by manipulating host chemical cues. If chemical cues of infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…For host density to affect haemocyte production and other measures of immune defences, snails must recognize that they are aggregating. In higher densities, snails could communicate by physical or chemical cues though our experiments focused on chemical communication because a number of studies have suggested that snails communicate through signaling molecules in snail-conditioned water (55,(79)(80)(81). We characterized fatty acids from snail water because several of them are the biosynthetic precursors of compounds that function in the immune defences of invertebrates and vertebrates (46,82).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For host density to affect haemocyte production and other measures of immune defences, snails must recognize that they are aggregating. In higher densities, snails could communicate by physical or chemical cues though our experiments focused on chemical communication because a number of studies have suggested that snails communicate through signaling molecules in snail-conditioned water (55,(79)(80)(81). We characterized fatty acids from snail water because several of them are the biosynthetic precursors of compounds that function in the immune defences of invertebrates and vertebrates (46,82).…”
Section: Discussionmentioning
confidence: 99%
“…There is an evolutionary benefit for a snail to respond prophylactically via cues from signaling molecules that more specifically indicate whether the risk is from a pathogen or parasite. However, much more research is needed to further understand the generality and strength of alterations to oxylipins in response to infection, how these may vary with host and parasite diversity, and how these changes may impact density-dependent prophylaxis ( 55 ). Further, studies on additional invertebrates are needed to understand the evolution of DDP and determine whether similar mechanisms are used across taxa.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations